Epidemiological research on radiation-induced cancer in atomic bomb survivors - Ozasa, Kotaro (J Radiat Res, 2016)
The late effects of exposure to atomic bomb radiation on cancer occurrence have been evaluated by epidemiological studies on three cohorts: a cohort of atomic bomb survivors (Life Span Study; LSS), survivors exposed in utero, and children of atomic bomb survivors (F(1)). The risk of leukemia among the survivors increased remarkably in the early period after the bombings, especially among children. Increased risks of solid cancers have been evident since around 10 years after the bombings and are still present today. The LSS has clarified the dose–response relationships of radiation exposure and risk of various cancers, taking into account important risk modifiers such as sex, age at exposure, and attained age. Confounding by conventional risk factors including lifestyle differences is not considered substantial because people were non-selectively exposed to the atomic bomb radiation. Uncertainty in risk estimates at low-dose levels is thought to be derived from various sources, including different estimates of risk at background levels, uncertainty in dose estimates, residual confounding and interaction, strong risk factors, and exposure to residual radiation and/or medical radiation. The risk of cancer in subjects exposed in utero is similar to that in LSS subjects who were exposed in childhood. Regarding hereditary effects of radiation exposure, no increased risk of cancers associated with parental exposure to radiation have been observed in the F(1) cohort to date. In addition to biological and pathogenetic interpretations of the present results, epidemiological investigations using advanced technology should be used to further analyze these cohorts.